CROSS-PLATFORM TECHNOLOGY COMPARISON ANALYSIS: FLUTTER & REACT NATIVE ON THE ANDROID PLATFORM - Jesica
In this Final Project, a comparison is conducted between the cross-platform technologies Flutter and React Native. Cross-platform technologies are widely used due to their advantage in developing applications across multiple platforms with a single codebase. Moreover, Flutter and React Native are the most commonly utilized cross-platform technologies at present. The comparison of these two frameworks is carried out to ascertain the strengths and weaknesses of each framework in terms of performance, user experience, and developer experience. To achieve this, two mobile applications are developed using each framework on the Android platform. Subsequently, testing and comparison are conducted on the two resulting applications. Testing involves various tools, including profiling tools for performance testing and UEQ for comparing user experiences. Meanwhile, the comparison of developer experience is performed by comparing the experiences during the application development process. In summary, the test results indicate that applications built with Flutter have more advantages in terms of performance and user experience. On the other hand, React Native applications demonstrate greater advantages in terms of developer experience. However, the obtained test results are heavily influenced by various factors such as Android versions, device specifications, and third-party libraries used. Therefore, it is advisable to conduct further research using state management libraries, different Android devices, or alternative platforms to obtain results that provide a more comprehensive depiction of both frameworks.